Key Characteristics and Examples of Digital Educational Content for an International Online Platform - Olesya V. Berseneva; Elena G. Doroshenko; Pavel S. Lomasko; Irina V. Trusey (Открытое образование (Москва))
Purpose of research. The research is aimed at identifying and scientifically substantiating the key characteristics of digital educational content for an international online platform that ensure effective teaching of Russian as a foreign language to citizens of Asian countries on the example of the Republic of Indonesia. The relevance of the paper is due to the intensification of academic ties between Russia and friendly countries of the Asia-Pacific region, which, according to state policy, requires the creation of effective digital solutions to promote Russian culture and education in the Russian language abroad. The key tasks were: analysis of the theoretical foundations of digital content development, expert assessment of the characteristics of digital content of existing mass educational platforms, designing a model of a typical online lesson and creating content examples based on the identified characteristics for asynchronous teaching of the Russian language to foreigners at the initial level.Materials and methods. The study used an integrated approach, including a theoretical analysis of scientific and pedagogical literature on the problem of developing digital educational content, a comparative analysis of leading international educational platforms according to criteria of coverage, the number of active users and the availability of Russian language courses. An expert assessment of the characteristics of the digital content of popular platforms was carried out according to the developed system of four quantitative and four qualitative parameters. The practical part of the study was based on the design and development of digital educational content using theoretically sound characteristics, modern information technology tools and specialized software.Results. Theoretically, the key characteristics of digital educational content are substantiated and systematized: multimodality of information presentation in text, graphic, audio and video formats; interactivity as the need for automated feedback; ergonomics, including consideration of typography (fonts and text layout), coloristic (harmony of color schemes); symmetry in the arrangement of educational objects in a modular grid and the amount of space occupied on the screen; clear and multilingual navigation. As well as the limitations of cognitive load in terms of the number of semantic units on the screen and the inclusion of the social component as an opportunity to communicate with real native speakers through audio and video messages in the forum. Based on the cognitive technology of full knowledge acquisition, a typical structure of an asynchronous online lesson of Russian as a foreign language is proposed, including five main and two additional stages. Examples are shown and the features of the main types of digital content for an international online platform are described: portable standardized interactive and multimedia packages, educational videos with native speakers, various types of interactive tasks with automated feedback, communicative elements for distributed communication.Conclusion. The conducted research allowed us to form a holistic view of the key characteristics and structural components of digital educational content for learning Russian as a foreign language in asynchronous online mode. The developed model and examples of content for a typical lesson take into account modern requirements for the organization of e-learning and are based on the principles of multimodality, interactivity, ergonomics of presentation of educational materials in combination with verified theoretical provisions of the cognitive approach.